S-BPM ONE - Education and Industrial Developments 4th International Conference, S-BPM ONE 2012, Vienna, Austria, April 4-5, 2012. Proceedings - Oppl, Stefan; Fleischmann, Albert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed proceedings of the industrial track of the 4th International Conference on Subject-Oriented Business Process Management, S-BPM ONE 2012, held in Vienna, Austria, in April 2012. S-BPM as a discipline is characterized by a seamless approach toward the analysis, modeling, implementation, execution, and maintenance of business processes, with an explicit stakeholder focus. The 19 papers included were selected from the practically oriented submissions, and they have gone through the same rigorous peer-review process as their scientific counterparts.
Keywords: Computer science; Organization; Planning; Information technology; Business -- Data processing; Computer Science; Information Systems Applications (incl. Internet).; IT in Business; Organization; Electronic books